The Structural Power of Reconfigurable Circuits in the Amoebot Model - Padalkin, Andreas; Scheideler, Christian; Warner, Daniel (28th International Conference on DNA Computing and Molecular Programming (DNA 28))

Fault-Tolerant Shape Formation in the Amoebot Model - Kostitsyna, Irina; Scheideler, Christian; Warner, Daniel (28th International Conference on DNA Computing and Molecular Programming (DNA 28))

Local Mutual Exclusion for Dynamic, Anonymous, Bounded Memory Message Passing Systems - Daymude, Joshua J.; Richa, Andréa W.; Scheideler, Christian (1st Symposium on Algorithmic Foundations of Dynamic Networks, SAND 2022, March 28-30, 2022, Virtual Conference)

Brief Announcement: The (Limited) Power of Multiple Identities: Asynchronous Byzantine Reliable Broadcast with Improved Resilience through Collusion - Götte, Thorsten; Scheideler, Christian (SPAA ’22: 34th ACM Symposium on Parallelism in Algorithms and Architectures, Philadelphia, PA, USA, July 11 - 14, 2022)

Brief Announcement: Fault-Tolerant Shape Formation in the Amoebot Model - Kostitsyna, Irina; Scheideler, Christian; Warner, Daniel (1st Symposium on Algorithmic Foundations of Dynamic Networks (SAND 2022))

2022 Edsger W. Dijkstra Prize in Distributed Computing - Aguiliera, Marcos; Richa, Andréa W.; Schwarzmann, Alexander A.; Panconesi, Alessandro; Scheideler, Christian; Woelfel, Philipp (PODC ’22: ACM Symposium on Principles of Distributed Computing, Salerno, Italy, July 25 - 29, 2022)

36th International Symposium on Distributed Computing, DISC 2022, October 25-27, 2022, Augusta, Georgia, USA

A self-stabilizing Hashed Patricia Trie - Knollmann, Till; Scheideler, Christian (Information and Computation)
While many research in distributed computing has covered solutions for self-stabilizing computing and topologies, there is far less work on self-stabilization for distributed data structures. However, when peers in peer-to-peer networks crash, a distributed data structure may not remain intact. We present a self-stabilizing protocol for a distributed data structure called the Hashed Patricia Trie (Kniesburges and Scheideler WALCOM'11) that enables efficient prefix search on a set of keys. The data structure has many applications while offering low overhead and efficient operations when embedded on top of a Distributed Hash Table. Especially, longest prefix matching for x can be done in O(log |x|) hash table read accesses. We show how to maintain the structure in a self-stabilizing way, while assuring a low overhead in a legal state and an asymptotically optimal memory demand of O(d) bits, where d is the number of bits needed for storing all keys.

Beep-and-Sleep: Message and Energy Efficient Set Cover - Götte, Thorsten; Kolb, Christina; Scheideler, Christian; Werthmann, Julian (Theor. Comput. Sci.)

Routing Schemes for Hybrid Communication Networks - Werthmann, Julian; Scheideler, Christian; Coy, Sam; Czumaj, Artur; Schneider, Philipp